2023
DOI: 10.1245/s10434-023-13339-0
|View full text |Cite
|
Sign up to set email alerts
|

Colon Cancer Disparities in Stage at Presentation and Time to Surgery for Asian Americans, Native Hawaiians, and Pacific Islanders: A Study with Disaggregated Ethnic Groups

Abstract: Background Vast differences in barriers to care exist among Asian American, Native Hawaiian, and Pacific Islander (AANHPI) groups and may manifest as disparities in stage at presentation and access to treatment. Thus, we characterized AANHPI patients with stage 0–IV colon cancer and examined differences in (1) stage at presentation and (2) time to surgery relative to white patients. Patients and Methods We assessed all patients in the National Cancer Database (NCDB) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Recent work by Jain et al. described colon cancer trends with a focus on time to surgery and analytic stage in a disaggregated Asian population (with Hmong as a unique subpopulation) using NCDB data 33 . Their work did not identify a statistical difference in time to surgery (in stage 0–III colon cancer cases) compared to a NHW population but noted a trend towards a higher stage in the Hmong population, like our findings.…”
Section: Discussionsupporting
confidence: 65%
“…Recent work by Jain et al. described colon cancer trends with a focus on time to surgery and analytic stage in a disaggregated Asian population (with Hmong as a unique subpopulation) using NCDB data 33 . Their work did not identify a statistical difference in time to surgery (in stage 0–III colon cancer cases) compared to a NHW population but noted a trend towards a higher stage in the Hmong population, like our findings.…”
Section: Discussionsupporting
confidence: 65%
“…Disaggregating health data are an important step in identifying and addressing barriers in access to care within specific subpopulations. 31,32 Our findings highlight the differences in cervical cancer stage at presentation among Hispanic/Latinx subpopulations and the heterogeneity of this group. We identified significant differences in income and education between Hispanic/ Latinx subpopulations.…”
Section: Discussionmentioning
confidence: 62%
“…13 Jain et al demonstrated similar findings with an increased time to surgery among Chinese, Japanese, Filipino, Korean, and Vietnamese patients when compared to white patients with colon cancer. 14 There is a controversy as to whether rural populations suffer a delay in surgical treatment of colon cancer compared with urban populations. Bosma et al found the time to surgery is longer for rural patients with CRC than for urban patients while Gaffley et al and Honaker et al found no difference in time to surgery.…”
Section: Discussionmentioning
confidence: 99%